An Early-Stage Experimental Study on the Contribution of TRM Components to Flexural Response - Gunes, Mustafa Esat; Girgin, Zehra Canan (TURKISH CHAMBER CIVIL ENGINEERS, 2026)
In this study, the influence of textile-reinforced mortar (TRM) systems on the out-of-plane flexural behavior of masonry elements is investigated through a small-scale experimental approach that offers a low-cost and rapid alternative to full-scale wall testing. Considering the multi-variable nature of TRM systems, twelve masonry beam specimens including ten strengthened configurations and two reference series were produced and tested in flexure to comparatively assess the contribution of different strengthening components. Two matrix types (natural hydraulic lime and cement-based mortars) and five textile reinforcements (glass(2), basalt, and carbon(2) fiber fabrics) were combined to examine how matrix-textile interaction governs the system response. The experimental program enabled the early-stage identification of behavioral trends among TRM systems by evaluating load-displacement relationships, energy dissipation capacities, and failure modes. The findings indicate that small-scale flexural testing provides an effective preliminary tool for distinguishing the relative performance of TRM configurations, particularly in terms of ductility and energy absorption. The study offers an experimental reference for selecting TRM components and highlights the performance tendencies associated with different matrix-textile combinations.
Keywords: Textile reinforced mortars; masonry wall strengthening; out-of-plane behaviour; cementitious composites; REINFORCED MORTAR TRM; MECHANICAL-PROPERTIES; WALLS; FABRICS; SYSTEMS; CARBON; FRP; Engineering